Mapping public debates about the climate security-mobility nexus in Mozambique: A social media analysis - Carneiro, Bia; Tucci, Giulia; Gomes, Frederico; Cruciata, Pietro; Resce, Giuliano (2023)
This working paper uses an online issue mapping approach to explore two research questions: 1) How is human mobility in Mozambique represented in local and international social media conversations? 2) What associations between human mobility and climate security-related topics are present in these public debates? Overall, results show diverging agendas between national and international actors, while also revealing that content disseminated about climate shocks and conflict events were less frequent but achieved the most engagement.